In vivo efficacy assessment of the CDK4/6 inhibitor palbociclib and the PLK1 inhibitor volasertib in human chordoma xenografts - Passeri, Thibault; Dahmani, Ahmed; Masliah-Planchon, Julien; El Botty, Rania; Courtois, Laura; Vacher, Sophie; Marangoni, Elisabetta; Nemati, Fariba; Roman-Roman, Sergio; Adle-Biassette, Homa; Mammar, Hamid; Froelich, Sébastien; et al. (Frontiers in Oncology, 2022)
Background Management of advanced chordomas remains delicate considering their insensitivity to chemotherapy. Homozygous deletion of the regulatory gene CDKN2A has been described as the most frequently genetic alterations in chordomas and may be considered as a potential theranostic marker. Here, we evaluated the tumor efficacy of the CDK4/6 inhibitor palbociclib, as well as the PLK1 inhibitor volasertib, in 3 chordoma Patient’s Derived xenograft (PDX) models to validate and identify novel therapeutic approaches. Methods From our chordoma xenograft panel, we selected 3 models, two of them harboring a homozygous deletion of CDKN2A/2B genes and another one a PBRM1 pathogenic variant (as control). For each model, we tested the palbociclib and volasertib drugs with pharmacodynamics studies together with RT-PCR and RNAseq analyses. Results For palbociclib, we observed a significant tumor response for one of two models harboring the deletion of CDKN2A/2B (p=0.02), and no significant tumor response in the PBRM1-mutated PDX; for volasertib, we did not observe any responses in the three tested models. RT-PCR and RNAseq analyses showed correlation between cell cycle markers and responses to palbociclib; finally, RNAseq analyses showed a natural enrichment of the oxidative phosphorylation genes (OxPhos) in the palbociclib-resistant PDX (p=0.02). Conclusion CDK4/6 inhibition appears as a promising strategy to manage advanced chordomas harboring a loss of CDKN2A/2B. However, further preclinical studies are strongly requested to confirm it and to understand acquired or de novo resistance to palbociclib, in the peculiar view of a targeting of the oxidative phosphorylation genes.